THE ROLE OF WORK MOTIVATION AND ORGANIZATIONAL CULTURE IN IMPROVING JOB SATISFACTION AND TEACHER PERFORMANCE IN RIMBA MELINTANG DISTRICT, RIAU, INDONESIA - Layla Hafni; David David; Kuswoyo Kuswoyo (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
This study aimed to determine the effect of work motivation, organizational culture and job satisfaction on teacher performance in Pubic Elementary schools in Rimba Melintang District, Riau Province, Indonesia. This analysis was conducted on 19 elementary schools with 190 respondents. The samples were taken and collected through a questionnaire. Data analysis used path analysis to analyze patterns of relationships between variables with the aim of knowing the direct and indirect effects of a set of exogenous variables (motivation and organizational culture) on endogenous variables (satisfaction and performance). The results showed that job satisfaction and teacher performance on motivation and organizational culture processed and tested using path analysis showed that there was an influence of motivation and organizational culture on satisfaction but not on employee performance. The novelty of this study lied in the results of data analysis. It indicated that partially, motivation and culture had a positive and significant influence on job satisfaction and performance but not so with the influence of motivation and work culture on performance through satisfaction. Motivation and organizational culture had no significant effect on performance based on the variable of job satisfaction. The study recommends that the schools should provide soft skills training (personality) and communication for teachers to act in accordance with religious, legal and social norms. They also should improve work ethic and responsibility. Educators also need to have an understanding that they are the role models in the community. Performance based benefits need to be formulated appropriately in order to improve the performance of the teaching staff.